2007
DOI: 10.1182/blood-2007-03-077057
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulins suppress T-cell priming by modulating the bidirectional interaction between dendritic cells and natural killer cells

Abstract: IntroductionIntravenous immunoglobulins (IVIgs) are pharmaceutical preparations of human IgG purified from pools of plasma of thousands of donors. For decades IVIgs have been established as treatment of autoantibody-mediated 1 and T-cell-mediated inflammatory disorders. 2 The distribution of IgG subclasses in IVIgs is comparable with that of IgG in normal human serum, however, unlike IgG purified from a single individual, therapeutic IVIg preparations contain substantial amounts of IgG dimers and traces of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 49 publications
3
44
0
2
Order By: Relevance
“…IVIG reduces cell surface expression of class II MHC on APCs (30,31). IVIG has also been shown to directly inhibit the ability of dendritic cells to prime naive T cells; this occurs through natural killer cell-mediated induction of antibody-dependent cellular cytotoxicity (32).…”
Section: Discussionmentioning
confidence: 99%
“…IVIG reduces cell surface expression of class II MHC on APCs (30,31). IVIG has also been shown to directly inhibit the ability of dendritic cells to prime naive T cells; this occurs through natural killer cell-mediated induction of antibody-dependent cellular cytotoxicity (32).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IVIG do not inhibit the proliferation of human T-cells in mice and support the hypothesis that IVIG reduce GvHD via immunomodulatory actions, as suggested by other authors. [38][39][40][41][42][43] Determination of human plasma cytokine concentration We found a strong increase of IFN-g, IL-17 and IL-2, and a moderate increase of IL-6, IL-8, IL-10 and IL-15 in PBStreated mice when compared with baseline levels (set as levels before huPBMC injection). This confirmed the generation of a human cytokine storm in our xenogeneic GvHD model.…”
Section: Ivig Did Not Reduce Human T-cell Proliferation In Micementioning
confidence: 97%
“…As inhibition of T-cell proliferation is one of the caveats of immunosuppression because it leads to the inhibition of the graft vs leukemia, this finding could have an impact on clinical practice. Many studies showed that IVIG inhibit T-cell proliferation or induce apoptosis 42,43,[53][54][55][56][57] whereas others failed to demonstrate any direct effect of IVIG on T-cells. 58,59 Interestingly, studies showing an inhibition of T-cell proliferation or an induction of apoptosis were performed in vitro whereas studies that failed to demonstrate any direct effect on T-cell proliferation were performed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that IVIg inhibited T-cell proliferation or induced apoptosis. [16][17][18][19][20][21][22] However, other studies reported the absence of effect of IVIg on T cells using alternative experimental conditions, making it difficult to derive strong conclusions on the role of IVIg on T-cell activation, proliferation, and survival. 16,[23][24][25] One possible explanation for the discrepant results could be that ex vivo allogeneic or polyclonal activation of purified cells by lectins, mitogens, or anti-CD3 antibodies is different from the physiologic context, leading to in vivo T-cell activation in response to an (auto)antigen.…”
Section: Introductionmentioning
confidence: 99%